2016
DOI: 10.1002/jobm.201500593
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycetes inhibit filamentous fungi from the cuticle of Acromyrmex leafcutter ants

Abstract: Actinomycetes bacteria associated with leafcutter ants produce secondary metabolites with antimicrobial properties against Escovopsis, a fungus specialized in attacking the gardens of fungus-growing ants, which denies the ants their food source. Because previous studies have used fungi isolated from fungus gardens but not from ant integument, the aims of the present study were to isolate actinomycetes associated with the cuticle of the Acromyrmex spp. and to quantify their inhibition abilities against the fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Inhibition tests in Petri dishes using A. ochraceus (among other fungal species) and five lineages of Pseudonocardia bacteria, one of which originated from the present work, showed that the controls exhibited greater average growth that differed significantly from that of the treated ants (Dângelo et al, 2016). This was verified by the formation of an inhibition halo caused by the antimicrobial substances produced by the bacteria.…”
Section: Mortality Testssupporting
confidence: 66%
“…Inhibition tests in Petri dishes using A. ochraceus (among other fungal species) and five lineages of Pseudonocardia bacteria, one of which originated from the present work, showed that the controls exhibited greater average growth that differed significantly from that of the treated ants (Dângelo et al, 2016). This was verified by the formation of an inhibition halo caused by the antimicrobial substances produced by the bacteria.…”
Section: Mortality Testssupporting
confidence: 66%
“…Increased abundance of Pseudonocardia on ants in response to parasite infection underscores the predicted function of this bacterium in the system: to protect the fungal cultivar against Escovopsis (Currie et al, 1999b(Currie et al, , 2003a. Pseudonocardia prevent Escovopsis infections of ant fungus gardens in vivo (Currie et al, 2003a;Little and Currie, 2008;Poulsen et al, 2010), and Pseudonocardia isolates consistently inhibit Escovopsis cultures in vitro (Currie et al, 1999b(Currie et al, , 2003aSchoenian et al, 2011;Meirelles et al, 2013;Sit et al, 2015;Dângelo et al, 2016). Some researchers have therefore suggested that these symbionts co-evolve with one another, locked in an arms race where Pseudonocardia and Escovopsis constantly evolve new mechanisms to gain an advantage over each other (Woolhouse et al, 2002).…”
Section: Pseudonocardia As a Defensive Symbiontmentioning
confidence: 98%
“…However, Pseudonocardia defenses against Escovopsis can vary (Poulsen et al, 2010), and some fungus-growing ants are not pathogenized by Escovopsis (Rodrigues et al, 2008), despite hosting Pseudonocardia. Further studies have shown that Pseudonocardia isolates have broad-spectrum activities against fungi other than just Escovopsis (Sen et al, 2009;Meirelles et al, 2013;Dângelo et al, 2016), suggesting that Pseudonocardia's antimicrobials inhibit diverse pathogens in the fungus-growing ant symbiosis.…”
Section: Pseudonocardia As a Defensive Symbiontmentioning
confidence: 99%
See 1 more Smart Citation
“…These actinomycetes were studied in assays against invading fungal species and were found to produce a suite of antifungals including antimycins, candicidin, dentigerumycin, and nystatin variants which suppress Escovopsis and other potential pathogens while leaving L. gongylophorus unharmed (Haeder et al, 2009; Seipke et al, 2012; Dângelo et al, 2016). More recently, Sit et al (2015) discovered, and chemically characterized, new antifungals related to dentigerumycin, called gerumycins, synthesized by Pseudonocardia spp.…”
Section: Use Of Actinomycete Natural Products By Fungus-farming Antsmentioning
confidence: 99%